The Prevalence of Dental Anomalies in the Western Region of Saudi Arabia. (19th June 2012) - Afify, Ahmed R.; Zawawi, Khalid H.
Abstract : Objective . The aim of this cross-sectional study was to investigate the prevalence of dental anomalies that could be a cause of malocclusion in the western region of Saudi Arabia. Materials and Methods . A retrospective study of 878 digital orthopantomograms (OPGs) taken of patients, age ranging between 12 and 30 years, who presented to treatment at the Faculty of Dentistry, King Abdulaziz University, Jeddah, Saudi Arabia between 2002 and 2011. The OPGs and dental records were reviewed for congenitally missing teeth, supernumerary teeth, impactions, ectopic eruption, transposition, germination, fusion, dilacerations, taurodontism, dens in dent, and any other unusual conditions that can be assessed with OPG. Results . The prevalence of patient that exhibited at least one dental anomaly was 396 (45.1%) patients. The prevalence of congenitally missing teeth was 226 (25.7%), impacted teeth 186 (21.1%), dilacerated teeth 10 (1.1%), supernumerary teeth 3 (0.3%), odontoma 1 (0.1%), and taurodontism was also 1 case (0.1%) of the total radiographs reviewed. Conclusions . Congenitally missing teeth were found to be the most prevalent anomaly (25.7%), and the second frequent anomaly was impacted teeth (21.1%), whereas root dilacerations, supernumerary teeth, and taurodontism were the least frequent anomalies (1.1%, 0.3% and 0.1%, resp.).